Brewer’s Spent Yeast (BSY), an Underutilized Brewing By-Product - Alice Jaeger; Elke K. Arendt; Emanuele Zannini; Aylin W. Sahin (Fermentation, 2020)
The repurposing of by-products and the reduction of waste from food processing streams is an ever-increasing area of interest. Brewer’s spent yeast (BSY) is a prevalent by-product of the brewing industry. The spent yeast cells are removed at the end of the bulk fermentation. A small amount of it is used to start the next batch of fermentation; however, the majority of the spent yeast is discarded. This discarded yeast is high in nutrients, in particular proteins, vitamins and minerals, as well as containing functional and biologically active compounds such as polyphenols, antioxidants, β-glucans and mannoproteins. At present, BSY is mainly used in animal feed as a cheap and readily available source of protein. This review explores alternative, value-added applications for brewer’s spent yeast including nutritional ingredients, functional food additives as well as non-food applications. A major challenge in the utilization of BSY in food for human consumption is the high level of RNA. An excess of RNA in the diet can lead to an increase in uric acid in the bloodstream, potentially causing painful health conditions like gout. This issue can be overcome by RNA degradation and removal via additional treatment, namely heat treatment and enzymatic treatment. There is potential for the use of BSY ingredients in various food applications, including meat substitutes, bakery products and savory snacks.